MAKNA RIMPU SEBAGAI MEDIA KOMUNIKASI NONVERBAL BAGI PEREMPUAN BIMA - Rahmi Rahmi (Universitas Mbojo Bima - Nusa Tenggara Barat, 2022)
This research is motivated rimpu culture which is one of the cultural community in general Bima, in which women wear to cover nakedness rimpu as Islam teaches that each of the women who have had to cover the nakedness “Aqil balik” in front of people who are not strange. In a society Simpasai sarimpu realized by using a form of obedience to Allah SWT. Rimpu culture began to be known since the advent of Islam in Bima brought by religious leaders from Gowa Makassar. Although the community it self knows no cultural Gowa rimpu so rimpu culture is the result of women’s culture, especially in Simpasai Bima. Rimpu is wearing gloves to wrap the head in which the wearer’s face visible only by using gloves. Rimpu is a type of clothing women’s clothing Simpasi in which a part of nonverbal communication. Rimpu in the context of nonverbal communication has its own meanings. As individual expression which through this rimpu communicate about the values that are believed to users. Is a personal identity or a particular social group. In addition, rimpu reflect the status of a woman in a community, he will be judged as a good woman and family well too if you wear rimpu. Rimpu also communicate the economic status of the wearer this can be seen from the type of glove wearing. Women who wear rimpu will also be assessed as a woman who religion because obedient to God Almighty to cover nakedness.